TINJAUAN PENANGANAN KASUS MALPRAKTEK MEDIS DI PENGADILAN PIDANA DALAM PERSPEKTIF HUKUM KESEHATAN - Albertus Soge (Justitia et Pax, 2019)
Legislation on Health Law is a Lex Specialist law that contains exceptional norms for legal protection for providers and receivers of health services. Law Number 36 of 2009 on Health and Law Number 29 of 2004 on Medical Practice are not used consistently in resolving medical malpractice cases in the Criminal Court, thus causing injustice and legal uncertainty. Incorrect application of the law and a long period of cases resolution in court requires reform in handling medical malpractice cases.